?EFFECT OF INITIAL CALLUS SIZE/QUANTITY, AGAR, PHYTAGEL ANDTHIAMINE ON FURTHER GROWTH OF LEAF AND PETIOLE-DERIVED CALLUS CULTURES OF GOSSYPIUMHIRSUTUM L. - AKHTAR, LAL HUSSAIN; MIRZA, M. ANWAR (Biological Sciences - PJSIR, 1997)
Effects of initial size of cotton callus on its further growth in vitro were investigated. It was observed that reduction in initial size/quantity of cultured callus resulted in reduced growth rate. Phytagel was found to be a superior gelling agent compared to agar.Thiamine at its higher concentration promoted the callus growth compared to the lower concentration.